Evaluation of trace element concentration in cancerous and non-cancerous tissues of human stomach. (October 2017) - Kohzadi, Shadi; Sheikhesmaili, Farshad; Rahehagh, Ramesh; Parhizkar, Baran; Ghaderi, Ebrahim; Loqmani, Hozan; Shahmoradi, Behzad; Mohammadi, Ebrahim; Maleki, Afshin
Abstract: Gastric cancer has a high mortality rate in west of Iran. Various environmental elements are proposed as cancer risk factors including trace elements. Trace elements can induce initiation or progression of carcinogenesis via oxidative stress and DNA injury. The aim of this study was to measure and compare some trace element concentration (Ca, Cu, Fe, As, Mg, Ni, Cd and Cr) in gastric cancer tissues and normal tissues. For this purpose, 35 patients with gastric cancer and 30 without any cancer were biopsied. Biopsies were taken from cancerous tissue and non-cancerous tissue of gastric cancer patients and gastric tissue of normal patients. The analysis of trace elements was performed using Inductively coupled plasma mass spectrometry (ICP-MS). Data analysis was carried out using SPSS and STATA 12 software. The research found that the concentrations of Fe, Mg, and As were higher in cancerous tissues compared with non-cancerous tissues whereas Cr, Cu, Ca, and Ni concentrations were higher in non-cancerous tissues of cancerous patients. When comparisons were made for cancer and normal samples, copper was the only metal, which was significantly higher in cancerous samples (p < 0.05) and Cr mean concentration in normal tissues was significantly higher compared with cancerous tissues (P = 0.02). Chi-Square test showed that there was no significant relationship in the demographic information between cancerous and normal patients except for location with K 2  = 7.604. Increased Cu and As concentration in gastric patients (both tissues) propose that these elements may have carcinogenic effects, although further study is suggested. Highlights: Trace element concentration was assessed in gastric cancer and normal tissues. Concentrations of Fe, Mg, and As were high in cancerous tissues. Cr, Cu, Ca, and Ni were higher in non-cancerous tissues of cancerous patients. The residence location of patients may play as an environmental factor. In general, Cu was significantly higher in cancerous samples (p < 0.05).